Response surface optimization of effects of some processing variables on carcinogenic/mutagenic heterocyclic aromatic amine (HAA) content in cooked patties - Dundar, Adnan; Saricoban, Cemalettin; Yilmaz, Mustafa Tahsin (ELSEVIER SCI LTD, 2012)
A five-factor Central Composite Orthogonal Design was adopted to study simultaneous effects of some processing variables such as NaCl (0-2%), fat (10-30%), ascorbic acid (0-600 ppm), cooking temperature (150-230 degrees C) and cooking time (5-15 min) on physicochemical properties and heterocyclic aromatic amine (HAA) contents of cooked beef patties. The HAAs analyzed were 2-amino-3-methylimidazo[4,5-f]-quinoline (IQ), 2-amino-3,8-dimethylimidazo[4,5-f]-quinoxaline (MeIQx), 2-amino-3,4-dimethylimidazo [4,5-f]-quinoline (MeIQ), 2-amino-3,4,8-trimethylimidazo[4,5-f]-quinoxaline (4,8-DiMeIQx) and 2-amino-1-methyl-6-phenylimidazo[4,5-b]-pyridine (PhIP), as quantified by high-performance liquid chromatography with photo-diode array detection (HPLC-UV/DAD). It was found that ascorbic acid decreased; however, fat, cooking temperature and time levels increased the contents of IQ MeIQx, MeIQ and PhIP. In addition, estimated ridge analysis was conducted to find values of the processing variables that maximize and minimize the five HAA contents, revealing that the results obtained would be useful for meat industry aiming to decrease HAA content in cooked meat products. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Heterocyclic aromatic amines (HAAs); Patty; Cooking temperature; HPLC-DAD/UV; Optimization; MUTAGENIC ACTIVITY; COOKING METHODS; MODEL SYSTEM; LEAN PORK; MEAT; CHICKEN; TEMPERATURE; RISK; FISH; Food Science & Technology